2022
DOI: 10.21062/mft.2022.060
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Measurement of Thermal Deformation of Tools on High-speed Machining Centers Based on Image Processing Technology

Abstract: In order to improve the efficiency of high-speed machining center and shorten its warm-up time, it is realistic and feasible to measure the thermal deformation of the machine tool system and then improve the machining accuracy of the machine by means of compensation. In this paper, a model XKA714B/A CNC milling machine and a 10mm diameter ball-head milling tool are selected. A high-speed camera is used to capture the gray level images of the tool when the machining center spindle speed is working at 1000 r/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…As a result, geometric error in the X direction of CNC machine movement was significantly reduced; however, the proposed compensation model did not consider the effect of cutting parameters and thermal expansion of CNC machine units, as well as cutting tool thermal expansion [23,24]. However, Zhao et al found that the thermal elongation of the cutting tool during the warming-up of a machine tool can reach up to 130 µm in the axial direction [25]. These findings were proved with finite element modeling (FEM) in Ansys software based on measuring spindle unit temperature with thermocouple sensors.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, geometric error in the X direction of CNC machine movement was significantly reduced; however, the proposed compensation model did not consider the effect of cutting parameters and thermal expansion of CNC machine units, as well as cutting tool thermal expansion [23,24]. However, Zhao et al found that the thermal elongation of the cutting tool during the warming-up of a machine tool can reach up to 130 µm in the axial direction [25]. These findings were proved with finite element modeling (FEM) in Ansys software based on measuring spindle unit temperature with thermocouple sensors.…”
Section: Introductionmentioning
confidence: 99%